Manajemen Kepala Madrasah dalam Mengembangkan Kinerja Guru dan Prestasi Siswa di Ma Hidayatul Mubtadi’in - Halimatus Sa’diyah (Attractive : Innovative Education Journal, 2024)
This research aims to analyze the role of madrasa head management in developing teacher performance and student achievement at MA Hidayatul Mubtadiin. Madrasah heads have a strategic role in creating a conducive learning environment and supporting improving the quality of education. This research uses a qualitative approach with a case study method. Data was collected through interviews, observation and documentation, then analyzed descriptively. The research results show that madrasa heads implement several strategies, such as professional development of teachers, empowering the management team, managing learning programs, and strengthening religious culture in madrasas. The implementation of effective management has been proven to increase teacher motivation and performance, which ultimately contributes to student academic and non-academic achievements. This study recommends the importance of leadership training for madrasa heads to increase competence in managing educational resources optimally